2016
DOI: 10.1186/s12883-016-0749-2
|View full text |Cite
|
Sign up to set email alerts
|

Help seeking behavior and onset-to-alarm time in patients with acute stroke: sub-study of the preventive antibiotics in stroke study

Abstract: BackgroundPatients with acute stroke often do not seek immediate medical help, which is assumed to be driven by lack of knowledge of stroke symptoms. We explored the process of help seeking behavior in patients with acute stroke, evaluating knowledge about stroke symptoms, socio-demographic and clinical characteristics, and onset-to-alarm time (OAT).MethodsIn a sub-study of the Preventive Antibiotics in Stroke Study (PASS), 161 acute stroke patients were prospectively included in 3 Dutch hospitals. A semi-stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
(42 reference statements)
0
12
0
1
Order By: Relevance
“…However, this study shows the positive relationship between SRH and the usage of both lay and professional care, which can be used to improve rural older patients' HSB by using limited resources in rural communities. For example, patients must understand when they should use lay or professional care to efficiently access health care resources [29,30]. In this process, they may be forced to modify their original HSB [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, this study shows the positive relationship between SRH and the usage of both lay and professional care, which can be used to improve rural older patients' HSB by using limited resources in rural communities. For example, patients must understand when they should use lay or professional care to efficiently access health care resources [29,30]. In this process, they may be forced to modify their original HSB [31].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies evaluating educational stroke campaigns have questioned whether improved knowledge can be transformed into symptom recognition and correct help-seeking behaviour at symptom onset, 32,33 and previous campaigns might have focussed too narrowly on stroke knowledge. Some studies have reported reduced prehospital delay and an increased number of patients treated with reperfusion therapy.…”
Section: Discussionmentioning
confidence: 99%
“…These health outcomes can be affected by their health and social conditions such as chronic diseases of various severities, healthcare accessibility, and treatment affordability. Previous studies have shown a relationship between HSB and clinical outcomes, such as brain stroke and heart failure, focusing on acute and emergency situations [ 12 , 27 , 28 ]. However, there has been no study on the relationship between HSB for mild symptoms and health outcomes, as well as aging [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%